Analisis Pengungkapan Biaya Lingkungan pada Pengelolaan Limbah Rumah Sakit Umum Daerah (RSUD) Toto Kabila, Bone Bolango - Istifani R. Sako; Ronald S Badu; Yustina Hiola (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the environmental cost disclosure in waste management at Toto Kabila Regional General Hospital (RSUD) Bone Bolango. The research method used is descriptive qualitative. The data used are primary and secondary data, with data collection using direct interviews and archival documents. The results of this study indicate that Toto Kabila Regional General Hospital (RSUD) Bone Bolango has incurred waste management costs as a form of maintaining environmental quality. Waste management costs incurred have not been specifically classified in the environmental cost report. However, in implementing environmental cost allocation, Toto Kabila Bone Bolango Regional General Hospital identifies environmental costs based on waste type, recognizes waste management costs when they provide benefits to the hospital, measures waste management costs using monetary units, presents waste management costs alongside other costs related to environmental costs, and discloses waste management costs in the operational report.